The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1371/journal.pone.0278907
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the association between epilepsy and depression: A systematic review and meta-analysis

Abstract: Objective This study offers meta-analytic data on the potential association between epilepsy and depression especially for the prevalence of depression in epilepsy or vice versa. Methods The relevant studies were searched and identified from nine electronic databases. Studies that mentioned the prevalence and/or incidence of epilepsy and depression were included. Hand searches were also included. The search language was English and the search time was through May 2022. Where feasible, random-effects models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
0
5
1
Order By: Relevance
“…Therefore, the difference in the assessment tools might overestimate the magnitude of depressive symptoms in our findings. This finding also had a significantly higher magnitude than other studies carried out in China (34%) ( 57 ), Australia (22.9%) ( 58 ) and America (23.1%) ( 18 ). The high prevalence of depressive symptoms reported in the studies under review suggests that the psychological toll of epilepsy may be particularly severe in low-income settings ( 59 , 60 ).…”
Section: Discussioncontrasting
confidence: 55%
“…Therefore, the difference in the assessment tools might overestimate the magnitude of depressive symptoms in our findings. This finding also had a significantly higher magnitude than other studies carried out in China (34%) ( 57 ), Australia (22.9%) ( 58 ) and America (23.1%) ( 18 ). The high prevalence of depressive symptoms reported in the studies under review suggests that the psychological toll of epilepsy may be particularly severe in low-income settings ( 59 , 60 ).…”
Section: Discussioncontrasting
confidence: 55%
“…One meta-analysis showed that more than 20 studies had reported that seizure frequency is a risk factor for depression ( 46 ). We also observed that seizure frequency was an independent risk factor for depression in both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, stigma contributes to the development of psychiatric comorbidities, such as anxiety and depression, and has a detrimental impact on the overall quality of life. Numerous studies indicate anxiety rates among epilepsy patients ranging from 31% to 56% [11], while depression rates range from 27% to 34%, with stigma being identified as a root cause of these psychological issues [12].…”
Section: Epilepsy and Stigmamentioning
confidence: 99%